2014
DOI: 10.5194/bgd-11-5997-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contrasting responses of terrestrial ecosystem production to hot temperature extreme regimes between grassland and forest

Abstract: Abstract. Observational data during the past several decades show faster increase of hot temperature extremes over land than changes in mean temperature. Towards more extreme temperature is expected to affect terrestrial ecosystem function. However, the ecological impacts of hot extremes on vegetation production remain uncertain across biomes in natural climatic conditions. In this study, we investigated the effects of hot temperature extremes on aboveground net primary production (ANPP) by combining MODIS EVI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Abrupt changes in climate factors, especially abrupt changes in extreme temperatures, have been pointed out as a major threat to ecosystems [27,28], because extreme temperature is an important physical restriction for some plants [29,30]. Several researchers investigated abrupt changes in the trends in temperature extremes in the northern hemisphere, North America, the northwest of China and mainland China [31][32][33][34][35]; for example, an abrupt change in both temperature and precipitation extremes in Northwest China occurred in around 1986 [34], but studies of the abrupt changes in temperature extremes in mainland China used the moderate extremes temperature indices based on the 10th (90th) percentiles.…”
Section: Introductionmentioning
confidence: 99%
“…Abrupt changes in climate factors, especially abrupt changes in extreme temperatures, have been pointed out as a major threat to ecosystems [27,28], because extreme temperature is an important physical restriction for some plants [29,30]. Several researchers investigated abrupt changes in the trends in temperature extremes in the northern hemisphere, North America, the northwest of China and mainland China [31][32][33][34][35]; for example, an abrupt change in both temperature and precipitation extremes in Northwest China occurred in around 1986 [34], but studies of the abrupt changes in temperature extremes in mainland China used the moderate extremes temperature indices based on the 10th (90th) percentiles.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation responses to drought were discernible across two markedly different biomes at a regional scale, with EVI reduced under drought conditions relative to baseline conditions in over 95% of shrub-steppe pixels and 80% of forest pixels. Drought sensitivity in this study likely reflected drought-induced changes to vegetation canopies—such as reductions in leaf area—that can interact with other drought-induced physiological stresses to impact ecosystem productivity 18 , 23 , 24 , 37 . The sensitivity of ecosystem productivity to climate variability has implications for ecosystem services and processes including habitat availability and stability through time, nutrient cycling and carbon storage, watershed hydrology, and diversity of species and plant functional groups 1 , 30 .…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have similarly found greater drought sensitivity in non-forest ecosystems relative to forested ones 28 and in semi-arid regions compared to humid ones 30 . Water-limited biomes with relatively low gross primary productivity have shown stronger coupling between hydroclimate variation and vegetation greenness 20 , greater productivity decreases in response to extreme precipitation patterns 26 and heat extremes 24 , and slower recovery after droughts 8 . Thus, at broad spatial scales spanning large climate gradients, our results agree with a general pattern of greater spectral sensitivity to drought in biomes with greater water limitation and lower biomass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations